LOLOSAN TAJUK, ALIRAN BATANG DAN INTERSEPSI PADA POHON PAKOBA (Syzigium sp.) NANTU (Palaquium obtusifolium Burck) DAN CEMPAKA (Magnolia tsiampacca) - Rumagit, Novita I.; Kalangi, J. I.; Saroinsong, F. B. (Universitas Sam Ratulangi, 2019)
Interception is one part of hidrology cycle which small value and sometimes ignored but interception has a large impact on certain plants. Amoun of value stem fall and through fall affected by interception. This study was conducted in Tomohon City Forest with purpose to determine magnitude of value through fall, stem fall and interception pakoba (Syzigium Sp.), nantu (Palaquium obtusifolium Burck) and cempaka (Magnolia tsiampacca). This research by using randomized group design method use 3 (tree) type of trees pakoba (Syzigium Sp.), nantu (Palaquium obtusifolium Burck) and cempaka (Magnolia tsiampacca). Each was repeated 5 (Five) times, in order to obtain 15 units of the experiment. Data were analyzed with analysis of variance and further using BNT test. The result of this research show amount of value stem fall pakoba 10,55 %, nantu 9,01 % and cempaka 7,99 %. Amount of value through fall pakoba 8,13 %, nantu 5,25 % and cempaka 2,45 %. Amount of value interception pakoba 82 %, nantu 86,31 % and cempaka 89,37 %. BNT test show interception in pakoba 82 % significant different with cempaka 89,37 % and not significant different with nantu 86,31 %. Nantu 86,31 % not significant different with cempaka 89,37 %.